Risks of concealing environmental degradation - Matt W. Hayward; Kaya Klop‐Toker; Salim Momtaz; Eliza Payne; Louisa Rebec; Robert J. Scanlon; Craig M. Shuttleworth; Nick Valentine; Andrea S. Griffin (Conservation Biology, 2026)
Current practice seeks to conceal the visual impact of land‐use change (i.e., development). Six percent of development impact assessments in Australia and 14% of the World Bank's assessments recommend visual impact mitigation. This mitigation results in, for example, vegetated buffer strips alongside cleared agricultural areas and earthen mounds that block environmental degradation from view. These measures make living alongside such development more palatable, but they conceal its negative effects from the general public. The scale of the problem is global with evidence of mandated regulatory drivers for concealment from around the world. These mitigation measures limit the emotional impact of development on people, reducing their likelihood of implementing pro‐environmental actions. It is important for the populace to see the scale of human impacts on the environment to increase the likelihood of pro‐environmental behaviors and decisions that will help ease the crises facing the environment. We recommend overtly exposing the public to environmental degradation to improve understanding of environmental impacts, increase environmental knowledge, trigger pro‐environmental emotions and actions, and help recalibrate people's understanding of biodiversity loss. Policies and research into the effect of creative public imagery designed to improve communication into environmental destruction while minimizing habituation are important, and ensuring that the “greening” of gray infrastructure yields genuine biodiversity benefits is also critical.